A Plague of Locusts? A Preliminary Assessment of the Threat of Multi-Drone Terrorism - Kallenborn, Zachary (Terrorism and political violence, 2023)
Emerging technologies provide new opportunities for terrorist organizations. Future terrorists may use multiple drones—either en masse or coordinated with each other in cruder or more sophisticated ways—to cause harm, potentially at scale. This study explores the topic via theoretical exploration and threat assessment. The first half explores relevant literatures on terrorist innovation; suicide bombing; airpower; and chemical, biological, radiological, and nuclear (CBRN) terrorism. The second half builds on the literature review to provide a systematic, albeit preliminary, threat assessment, examining the threat as a function of motivations and capabilities, and elucidates the characteristics of groups that may be drawn to this technology. Policy recommendations to ameliorate this emerging threat conclude.